Novel Role of Dehydrated Human Amnion/Chorion Membrane in Healing of Denuded Ureter in Robot-Assisted Excision of Endometriosis - Osamah Hasan; Grant S. Johnson; James J. Siegert; Francisco Garcini; Thai T. Nguyen (Hindawi Limited, 2019)
Ureteral injury is an uncommon but potentially morbid complication following any open or endoscopic pelvic procedure. Gynecologic surgeries alone make up 50 percent of nonurologic ureteral injuries leading to prolonged hospital stays, secondary interventions, and potential loss of renal function. The use of AmnioFix ® a processed dehydrated, immunologically privileged cellular amniotic membrane allograft has been well established in urologic and gynecologic procedures. These allografts contain human extracellular matrix components, growth factors, and cytokines that mediate inflammation and facilitate would healing. We report the first application of AmnioFix on a denuded ureter during a case of robotic-assisted excision of endometriosis. We include a literature review and discussion on the management outcomes of iatrogenic injury to the ureters.